2021
DOI: 10.12659/msm.934679
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cell-Free Mitochondrial DNA: A Potential Blood-Based Biomarker for Sarcopenia in Patients Undergoing Maintenance Hemodialysis

Abstract: Background Mitochondrial impairment and exaggerated inflammation are hallmarks of sarcopenia. Recently, cell-free mitochondrial DNA (cf-mtDNA) has been in the spotlight as an endogenous danger molecule that can potentially elicit inflammation. Yet, its actual impact on sarcopenia, especially in patients with maintenance hemodialysis (MHD), is still at an early stage of investigation. Material/Methods A total of 105 MHD patients were enrolled in this study. The subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Especially in chronic inflammatory conditions, mitochondrial DNA is released into plasma and serum as a result of cell stress and tissue damage and leads to activation of inflammation by using TLR 9 pathway with increasing serum levels [13]. In a study conducted by Zhen Fan et al in 2022, it was reported that serum cell free mitochondrial DNA level was significantly higher in the group with sarcopenia than in the group without sarcopenia in a population of 105 patients undergoing haemodialysis as renal replacement therapy due to chronic renal failure [14]. Sarcopenia is an age-related syndrome marked by the loss of muscle mass and function, with unclear mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in chronic inflammatory conditions, mitochondrial DNA is released into plasma and serum as a result of cell stress and tissue damage and leads to activation of inflammation by using TLR 9 pathway with increasing serum levels [13]. In a study conducted by Zhen Fan et al in 2022, it was reported that serum cell free mitochondrial DNA level was significantly higher in the group with sarcopenia than in the group without sarcopenia in a population of 105 patients undergoing haemodialysis as renal replacement therapy due to chronic renal failure [14]. Sarcopenia is an age-related syndrome marked by the loss of muscle mass and function, with unclear mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…cf-mtDNA exists in different biofluids, such as urine [ 83 ], blood [ 84 ], saliva [ 81 ], cerebrospinal [ 85 ], and follicular fluid [ 86 ]. MtDNA is supposed to be more prone to damage than nuclear DNA.…”
Section: Cell-free Dna In Sars-cov-2 Infectionmentioning
confidence: 99%
“…Plasma mtDNA is a strong predictor of cardiovascular events as well as the need for hospitalization in patients with peritoneal dialysis [ 64 ]. In patients undergoing maintenance hemodialysis (MHD), circulating mtDNA contents were significantly higher in sarcopenia patients, together with higher TLR9 and IL-6 expression, which demonstrated that mtDNA could be involved in the pathogenesis of MHD-related sarcopenia [ 65 ]. As one of the indispensable proteins encoded by mtDNA, serum ND6 was increased in active antineutrophil cytoplasmic antibody-associated vasculitis, and ND6 concentration was negatively correlated with the percentage of normal glomeruli in kidney biopsies [ 66 ].…”
Section: Mtdna Distribution In Kidney Diseasesmentioning
confidence: 99%